Ginastera (1916–1983): The progress of a method. (Revista Argentina de Musicología, 2014)
In general terms, the musical poetics of Alberto Ginastera (1916–1983) subsumes seminal 20thcentury compositional procedures, which, in turn, served to develop analytical systems based on studies of canonic composers. The labyrinthine interpenetration that emerges from the process of transferring and recomposing materials from one work to another, inherent to the progress of Ginastera’s method, can involve a generative element taken from a previous work or an entire enunciation re-elaborated as metamorphosis, creating a dense web of intratextual relationships, which, projected at different levels of his compositions, turns each presentation into a “work in progress”. From an analysis of the Segundo Cuarteto de Cuerdas (1958) that probes its structural properties, its cryptography, and its dialogical relationships with paradigms of the genre, as well as the quartet’s arrangement or Bearbeitung as Concerto per corde, Op. 33 (1965), this inquiry broadens its scope to other cases of “recomposition” and the analytical systems subtending them in a partial attempt to map the vast intratextual web permeating Ginastera’s creative journey, which itself verifies the congruence between his poetics and the approaches to musical construction that defined modernity in the twentieth century.
Keywords: Alberto Ginastera; Segundo Cuarteto de Cuerdas, Op. 26 (1958); Alban Berg; Lyric Suite (1926); Bearbeitung; analytical systems; sources